Concentration-compactness principle for variable exponent spaces and applications - Fernandez Bonder, Julian (2010)
In this article, we extend the well-known concentration - compactness principle by Lions to the variable exponent case. We also give some applications to the existence problem for the p(x)-Laplacian with critical growth.